Conider the equation given below;
![6x+2y=13](https://img.qammunity.org/2023/formulas/mathematics/college/wo6hnbcktevjb0fqww5c3n90iixfw1dyuw.png)
To express this equation in the form
![y=mx+b](https://img.qammunity.org/2023/formulas/mathematics/high-school/smsb8cbft03lwblmi49nf2l6jby2ofxzws.png)
We shall begin by making y the subject of the equation, a follows;
![\begin{gathered} 6x+2y=13 \\ \text{Subtract 6x from both sides;} \\ 6x-6x+2y=13-6x \\ 2y=13-6x \\ \text{Divide both sides by 2, and you'll have;} \\ (2y)/(2)=(13-6x)/(2) \\ y=(13-6x)/(2) \\ \text{Simplify the right side;} \\ y=(13)/(2)-(6x)/(2) \\ y=(13)/(2)-3x \\ \text{Written in the slope-intercept form, it now becomes;} \\ y=-3x+(13)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mt9rt6o9qq1aj8i7lkpfhf9lcvqhselcpn.png)
The values of m and b are;
![\begin{gathered} y=mx+b \\ y=-3x+(13)/(2) \\ \text{Hence;} \\ m=-3,b=(13)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ac9bha99rxghursr3d5co1c4ncvzqz1keg.png)
Part B:
Therefore, for a point on this line where x = 2, we would have;
![\begin{gathered} y=-3x+(13)/(2) \\ \text{Substitute for the value of x}=2 \\ y=-3(2)+(13)/(2) \\ y=-6+(13)/(2) \\ y=(13)/(2)-6 \\ \text{Take the LCM of both numbers and we'll now have;} \\ y=(13-12)/(2) \\ y=(1)/(2) \\ \text{Therefore the ordered pair would be;} \\ (2,(1)/(2)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/784ylyatr0i8b0yf61gxrz1wss03cw416q.png)
ANSWER:
Part A;
![y=-3x+(13)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/u9xiuiep0pwysscr6jchosh8ynsm3zo71x.png)
Part B:
![(2,(1)/(2))](https://img.qammunity.org/2023/formulas/mathematics/college/2rf7ywcpjd4mjc0rnq87jgz1vbabg8unrn.png)